The Influence Model Blanded Learning of Social Sciences Subjects Respecting Indonesian Ethnic and Cultural Diversity To Increasing Activity And Learning Outcomes of Grade V Students in Elementary School 1 Purwoharjo Banyuwangi Distric Year 2015/2016 - Ari Susandi (Pancaran Pendidikan, 2017)
Education is an attempt to develop knowledge and form a golden generation of Indonesian character. To achieve this, we need educators who are reliable and able to create new innovations that education in Indonesia is growing and quality. By developing the approach here blended Learning students not only see and learn about things around them, but they are required to master all the resources and extensive knowledge, one of them with controlled study with an integrated learning system to capitalize on IT as a learning medium. By applying lessons blended learning in social studies subject of ethnic and cultural respect Indonesia has been an increase of 78,91% students learning activities that initially only 46.57% and improve learning outcomes as much as 78,6% which was initially only 68,35% V class at SDN 1 Purwoharjo Banyuwangi. Many of the benefits gained by teachers and students in the learning process in the classroom and to improve the productivity of teachers in developing information technology more accurate, especially in the field of education.